The association between mentoring and training outcomes in junior doctors in medicine: an observational study. Issue 9 (21st September 2018) - Ong, John; Swift, Carla; Magill, Nicholas; Ong, Sharon; Day, Anne; Al-Naeeb, Yasseen; Shankar, Arun
Abstract : Objective: To determine quantitatively if a positive association exists between the mentoring of junior doctors and better training outcomes in postgraduate medical training within the UK. Design: Observational study. Participants: 117 trainees from the East of England Deanery (non-mentored group) and the recently established Royal College of Physicians (RCP) Mentoring scheme (mentored group) who were core medical trainees (CMTs) between 2015 and 2017 completed an online survey. Trainees who received mentoring at the start of higher specialty training, incomplete responses and trainees who were a part of both the East of England deanery and RCP Mentoring scheme were excluded leaving 85 trainees in the non-mentored arm and 25 trainees in the mentored arm. Responses from a total of 110 trainees were analysed. Main outcome measures: Pass rates of the various components of the Membership of the Royal College of Physicians (MRCP) (UK) examination (MRCP Part 1, MRCP Part 2 Written and MRCP Part 2 PACES), pass rates at the Annual Review of Competency Progression (ARCP), trainee involvement in significant events, clinical incidents or complaints and trainee feedback on career progression and confidence. Results: Mentored trainees reported higher pass rates of the MRCP Part 1 exam versus non-mentored trainees (84.0% vs 42.4%, p<0.01). Mentored international medical graduates (IMGs) reported higher pass rates than non-mentored IMGs in the MRCP Part 2 Written exam (71.4% vs 24.0%, p<0.05). ARCP pass rates in mentored trainees were observed to be higher than non-mentored trainees (95.8% vs 69.9%, p<0.05). Rates of involvement in significant events, clinical incidents and complaints in both groups did not show any statistical difference. Mentored trainees reported higher confidence and career progression. Conclusions: A positive association is observed between the mentoring of CMTs and better training outcomes. Further studies are needed to investigate the causative effects of mentoring in postgraduate medical training within the UK.